The Correlation between Single Nucleotide Polymorphisms (SNPs) rs360719 and rs1012356 with IL-18 and IL-22 Gene Expression in Iraqi SLE Patients - Noor, Aso A. Mohammed; Mahmood, Aseel S. (Iraqi Journal of Science, 2026)
Systemic Lupus Erythematosus (SLE) is a multisystemic autoimmune illness distinguished by biological and clinical variability. Interleukin-18 (IL-18) is a cytokine linked to some immunological responses, and elevated amounts of IL-18 have been found in autoimmune animal models and the biological fluids and organs of people with various autoimmune diseases, previous studies have indicated the importance of IL-22 (another interleukin) in the development and pathogenesis of several autoimmune diseases, including SLE. This study investigates the molecular correlation between gene expression of both IL-18 and IL-22 and different genotypes of rs360719 and rs1012356 SNPs, exploring their roles in the pathogenesis of SLE in a sample of Iraqi patients. By analyzing samples from 63 SLE patients and 42 health controls, the study investigated the expression levels of IL-18 and IL-22 expression through the qRT-PCR technique. The results of gene expression represented by fold change (2-ΔΔCt) revealed an increased expression of IL-18 mRNA in total SLE patients, but such increase was not significantly different between male and female groups. The results obtained also suggest that there is no association between SLE and IL-22 rs1012356, and the data obtained show that the IL-18 rs360719 polymorphism may be associated with susceptibility to SLE and the expression levels of both genes were higher in female SLE patients than in female controls, indicating that these cytokines might have a role in the disease's preponderance in females. By providing possible biomarkers for early detection, prognosis, and the development of targeted therapeutics, the study paves the way for additional research into the molecular pathways of these molecules with the goal of improving the care and results for SLE patients in Iraq.